Integrating Soft Skills Assessment Through Soft Skills Workshop Program for Engineering Students at University of Pahang: An Analysis - Rashidi, Abbas; Fakhrul Adabi, Abdul Kadir; Ilhamie, Abdul Ghani Azmi (IJRSS & K.A.J., 2013)
The objective of this paper is to address the need for implementing Soft Skills Workshop that could be an instrumental in developing and improving Soft Skills Program in UMP. The UMP Soft Skills components consist of Positive Values, Leadership, Team Working, Oral Communication, Written Communication, and Learning Capabilities. Hence, the Soft Skills Expert Group at the Centre for Modern Languages & Human Sciences, UMP took the initiative in organizing the Soft Skills 2 Workshop for final year students before they set out for their industrial training. This program was organized to unveil the awareness of employability skills and industrial requirements that should be attained by students in their industrial training as well as for their future career development. Throughout the talk sessions, which based on the modules, group activities and assessments, this workshop aims to instil and nurture the Soft Skills components within the students. A total of 226 final year Engineering students out of 549 were selected as respondents. The study was conducted using survey methods. The descriptive methods of statistical data analysis were utilized. Based on the analysis of the findings, generally it was found that the majority of the respondents were agreed to the implementation process of the Soft Skills workshop. Most of them (more than 50%) stated that the “strongly agree” and “agree” results to all question asked. Thus, this paper addresses a comprehensive and integrated model in fulfilling the needs of final year students as well as stakeholders and governing agencies/bodies in order to produce proficient, expert and wellcompetent graduates in academic, technical skills and non-technical skills.